Comprehensive analysis of effects of dynamic load frequency and hydrogenation to instigate White Etching Areas (WEAs) formation under severe sliding condition of bearing steel. (April 2020) - Sreeraj, K.; Ramkumar, P.
Abstract: This study investigates the effect of loading frequency and hydrogenation to instigate the White Etching Areas (WEAs) formation under severe sliding condition of bearing steel. Experiments were carried out at 1.5 Hz and 4.5 Hz loading frequencies by varying the contact pressure from 1 to 2 GPa using dynamic load Pin-on-Disc (PoD) tribometer. Steel-on-steel tribo-pair was lubricated by two different lubricants, PAO and real-time hydrogenating oil, under boundary lubrication. Synergic interaction between hydrogen enhanced and mechanical stress induced drivers on WEAs formation was established. Subsequently, quantitative insights on the catalysing behaviour of the individual and concurrent actions of drivers were elucidated. Sequential evolution of butterfly around the non-metallic inclusion from the primitive stage was revealed in pure sliding through metallographic investigation. Graphical abstract: Image 1 Highlights: Successfully replicated WEAs formation without hydrogenation using dynamic load PoD tribometer under pure sliding condition. Quantitative insight on synergic interaction of hydrogenation and mechanical drivers on the WEAs formation was revealed. Combined effect of hydrogenation and loading frequency enhances WEAs formation within shortest cycles of 0.178 ×10 6 Butterfly effect around the inclusion under pure sliding with dynamic loading condition was established for the 1 st time.